Abstracts of the 43rd Annual Scientific Meeting of the Nutrition Society of Australia - Sandra Iuliano; Kirrilly Pursey; Rebecca Haslam; Alison Coates (Proceedings, 2020)
The 43rd Annual Scientific Meeting of the Nutrition Society of Australia was held in Newcastle, Australia, from 2 to 5 December 2019. The theme of the meeting was Nutrition: The Epicentre of Health. Abstracts were submitted from 24 countries. The conference was attended by 250 registrants and 208 papers were presented consisting of 16 plenary, 91 oral and 101 poster presentations. This issue presents the proceedings of this meeting in the form of abstracts of papers presented at the conference.